2017
DOI: 10.14814/phy2.13123
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms underlying the muscle metaboreflex modulation of sweating and cutaneous blood flow in passively heated humans

Abstract: Metaboreceptors can modulate cutaneous blood flow and sweating during heat stress but the mechanisms remain unknown. Fourteen participants (31 ± 13 years) performed 1‐min bout of isometric handgrip (IHG) exercise at 60% of their maximal voluntary contraction followed by a 3‐min occlusion (OCC), each separated by 10 min, initially under low (LHS, to activate sweating without changes in core temperature) and high (HHS, whole‐body heating to a core temperature increase of 1.0°C) heat stress conditions. Cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(144 reference statements)
2
4
0
Order By: Relevance
“…Consistent with the recent study under resting hyperthermic conditions in non‐endurance trained young males (i.e., exercised for no more than 2–3 times per week for 30 min duration) (Haqani et al. ), we observed that COX inhibition does not alter sweat rate during passive heating in untrained individuals and extend upon this observation by demonstrating a similar response in endurance‐trained individuals (Fig. ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with the recent study under resting hyperthermic conditions in non‐endurance trained young males (i.e., exercised for no more than 2–3 times per week for 30 min duration) (Haqani et al. ), we observed that COX inhibition does not alter sweat rate during passive heating in untrained individuals and extend upon this observation by demonstrating a similar response in endurance‐trained individuals (Fig. ).…”
Section: Discussionsupporting
confidence: 92%
“…Inconsistent with the present observation, it was reported that NOS inhibition does not modulate sweating response at a similar elevations in core temperature (i.e., 1.0°C) during passive heating (Haqani et al. ). While the underlying reason(s) for this discrepancy is unknown, it is assumed that individual differences in the contribution of NOS to sweating may in part be a factor.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations